Problematic of Implementation of Electronic GMS on Deeds Made by Notaries - Absori Absori; Aidul Fitriciada Azhari; Kelik Wardiono; Syifa Rana Tsary; Silaas Oghenemaro Emovwodo (Fakultas Hukum Universitas Mataram, 2022)
The study reviewed the development of the digital era in the legal field, especially The Electronic General Meeting of Shareholders (GMS), which is ruled by law. The problem formulation was how the electronic GMS, according to positive law in Indonesia, and how the impact on the notarial deed related to its implementation. The method used by the researcher was normative and library study based on the primary material (legislation), secondary material (scientific works, journals, books, documents, and other literature), and tertiary legal materials (legal dictionaries). The study results were that E-GMS is effective today, then regulated in Art 77 UUPT and PJOK Number 16/Pojk.04/2020, so that the Limited Liability Company members can carry out the GMS as usual without being physically present to break the chain of the Covid-19 pandemic. Although the e-GMS arrangements have been regulated in the legislation, the lex specialist derogat lex generalist principle cannot be ignored; article 16 paragraph (1) letter (m) and Article 18 UUJN are still prioritized so that the electronic deed of the GMS cannot be carried out or will resulting in the legal force of the proof being a private deed.